USING OF EXPLICIT INSTRUCTION METHOD IN IMPROVING STUDENTS’ GRAMMAR ABILITY IN SIMPLE PRESENT TENSE AT CLASS X3 OF SMA NEGERI 4 LEIHITU - Ernita Lumaela; Stella Rose Que (JURNAL TAHURI, 2021)
Based on the preliminary study, almost students usually have some problems in finding out the verb form of simple present tense. There are omissions of be, and suffix -s/-es. It shows that students’ grammar ability is low in simple present tense. The research questions are how can explicit instruction method improve students’ grammar ability in simple present tense? And what are students’ responses about using explicit instruction method during teaching learning process? Its significant are for students, they have grammar ability in using simple present tense well. And they are accustomed to use the correct verb of simple present tense. Then, for teacher, is to provide the better method for teaching grammar. And the Explicit Instruction method helps the teacher to variety his or her instruction of teaching grammar. Type of this research is classroom action research by using Explicit Instruction method. It is conducted at SMA Negeri 4 Leihitu in Seith village of Central Maluku. The subject is the first grade of class X3 with the total number 20 students. The research has been done in three cycles consisted of three times of meeting in each cycle during four weeks. And every last meeting of each cycle, researcher conducted a test to measure students’ improvement. And the pre- test of students’ result show the mean 29,5 at the poor level. Then, in the first cycle, the students’ mean add 52,9 at the poor level. And the second cycle, the students’ mean increase 65 which show at the average level. And the last cycle, students’ mean improve highly 78 which shows at the good level. Finally, students show the good progress. They have been able to use the simple present tense of auxiliary verbs in sentences, determine the correct verbs of the subject-verb-agreement and transform the verb of the third singular person well